Child-care web-based application / Nur Izzati Ayub - Ayub, Nur Izzati (2021)
Child-care most the important part in the daily life as parents because against child. In addition, child care also have protect at the kindergarten like covers all aspects such as physical, emotional, social, language and also have the cognitive development. Therefore, the early education needs well conducted which to professional development practice in the process development including area in need of investigation that can inform the early childhood education how to perform the development effort in their influence skill and behavior. Furthermore, child care also part of important thing in the family to make sure children safe from the environment kindergarten. It also discuss the importance and impact of information and communication technology on teaching and learning process in the kindergarten for the children. To solve the problem, web based application are produced. The aim of this research is develop child-care web-based application. To achieve the aim of the study there are three objectives that will be done which is to identify the registrated child care in Perlis, to develop child care web based application using the ArcGIS Online and lastly to analyses the user satisfaction of child care web based application. The data used in this research are based map Perlis, data of child care from the Jabatan Kuasa Masyarakat (JKM). Meanwhile, software used in this research are Excel, ArcGIS, ArcGIS Online, Server XAMPP and Sublime Text. At the end of this result, child care web based application can run successful.